Physical And Organoleptic Characteristics Of Semprong Cookies Substitution Of Dahlia Tuber Flours (Dahlia Pinnata) - Putri Amelia (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This study aims to determine the physical characteristics (thickness, water absorption, and drying loss) and organoleptic characteristics (color, aroma, texture, taste, and overall) of semprong cake substituted with dahlia flower tuber flour. The semprong cake in this study has a filling, namely chocolate jam which is given the addition of 15% dahlia flower tuber flour. This study used a completely randomized design (CRD) for physical quality consisting of 4 types of treatment and 3 replications, namely P0 (100%), P1 (90%: 10%), P2 (85%: 15%), P3 (80 %: 20%). To produce 12 treatment units. The data were analyzed using Analysis of Variant One Way (ANOVA) with a significance level of 95%. For organoleptic quality, the Quantitative Descriptive Analysis (QDA) test was used with a 15 cm long line scale. The results of the data are analyzed and then transformed into a spider web graph. Substitution of dahlia flower tuber showed a significant difference in the aspects of thickness, water absorption, and drying loss. Meanwhile, the organoleptic quality has a significant effect on the aspects of color, aroma, and taste. However, in the overall aspect, the panelists prefer P2 (15%), so it can be concluded that the P1, P2, and P3 semprong cake products have the same physical quality as the untreated semprong cakes and P2 is preferred by the panelists in organoleptic quality assessment.